Crystallization behavior and electroactive properties of PVDF, P(VDF-TrFE) and their blend films. (February 2017) - Jia, Nan; He, Qian; Sun, Jing; Xia, Guangmei; Song, Rui
Abstract: PVDF, poly(vinylidene fluoride), as a semi-crystalline polymer, has interesting electroactive properties but usual melt and solution processing techniques result in its thermodynamically favored non-polar α-phase. By comparison, poly(vinylidene fluoride-trifluoroethylene) P(VDF-TrFE), PT for short, directly crystallizes in the polar β-phase under the same conditions as PVDF. In this study, blend thin films comprising PVDF and P(VDF-TrFE) were prepared by solvent casting method. The difference in the crystallization behavior is comprehensively investigated between the polymers: PVDF, P(VDF-TrFE), and the resulting blend films. It is found that replacement of the fluoride atom in TrFE monomer induces a strong steric hindrance that may alter the crystallization process to become more favorable for nucleation of the PVDF β-phase. To figure out the effect of TrFE content on the crystallization behavior and electroactive properties, films with different blend ratios of PVDF and P(VDF-TrFE) were prepared. We found that the PVDF films exhibit higher crystallization activation energy (Δ E ) as PT content increases. The atomic force microscopy (AFM) in the piezoresponse force microscopy (PFM) mode illustrated that P5T5 films with equal contents of PVDF and P(VDF-TrFE) induced the highest d 33 values.